The Cyber Kill Chain Model and Its Applicability on The Protection of Students Academic Information Systems (SAIS) in Tanzanian HEIs - Matto, George (Universitas Bina Darma, 2024)
Security threats are constantly evolving in various computerized systems. As in many other systems, security threats and attacks have been directed to Students Academic Information System (SAIS) in Higher Education Institutions (HEIs). The seven steps cyber kill chain model offers preventive defense against such security threats. Little is known, however, on how well the model is applicable in the protection of SAIS. This study was therefore carried out to investigate the applicability of the cyber kill chain model on the protection of SAIS. The study was qualitative in which empirical evidence from literature was employed to gather data which were then analysed thematically through content analysis. Results showed that the cyber kill chain model is very relevant and applicable in the protection of SAIS. Each of the seven steps of the model practically applies differently in SAIS which entails for distinct protective measures as detailed in the paper. The study calls upon HEIs stakeholders to leverage the proposed preventive measures against security threats in SAIS.